2019
DOI: 10.3847/1538-4357/ab07b2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Atom Reactions with C2H6, C2H4, and C2H2 in Ices

Abstract: Oxygen atom addition and insertion reactions may provide a pathway to chemical complexity in ices that are too cold for radicals to diffuse and react. We have studied the ice-phase reactions of photoproduced oxygen atoms with C2 hydrocarbons under ISM-like conditions. The main products of oxygen atom reactions with ethane are ethanol and acetaldehyde; with ethylene are ethylene oxide and acetaldehyde; and with acetylene is ketene. The derived branching ratio from ethane to ethanol is ∼0.74 and from ethylene to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 76 publications
4
40
0
Order By: Relevance
“…As reported in Chuang et al (2020), ethylene oxide, with the highest internal energy among the three C 2 H 4 O isomers, is absent in the present work. This result also confirms the proposed formation channel of ethylene oxide, which can be only produced in C 2 H 4 containing ice reacting with O-atoms under ISM-like conditions (Bennett et al 2005b;Ward & Price 2011;Bergner et al 2019). The hydrogen saturated product ethanol is identified by its nonoverlapped IR peaks at 1046 and 1088 cm −1 that correspond to the CO stretching modes (ν 11 ) and CH 3 rocking mode (ν 10 ), respectively (Barnes & Hallam 1970;Mikawa et al 1971;Boudin et al 1998).…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…As reported in Chuang et al (2020), ethylene oxide, with the highest internal energy among the three C 2 H 4 O isomers, is absent in the present work. This result also confirms the proposed formation channel of ethylene oxide, which can be only produced in C 2 H 4 containing ice reacting with O-atoms under ISM-like conditions (Bennett et al 2005b;Ward & Price 2011;Bergner et al 2019). The hydrogen saturated product ethanol is identified by its nonoverlapped IR peaks at 1046 and 1088 cm −1 that correspond to the CO stretching modes (ν 11 ) and CH 3 rocking mode (ν 10 ), respectively (Barnes & Hallam 1970;Mikawa et al 1971;Boudin et al 1998).…”
Section: Methodssupporting
confidence: 85%
“…For example, Hawkins & Andrews (1983) reported the formation of three different C 2 H 4 O isomers (i.e., acetaldehyde, vinyl alcohol, and ethylene oxide) and ketene upon photolysis of C 2 H 4 :O 3 in an Ar matrix at 15-20 K. Similar products (with exception of ketene) have also been found in electron-induced suprathermal O-atom experiments using a C 2 H 4 :CO 2 ice mixture (Bennett et al 2005b). Recent laboratory research by Bergner et al (2019) studying the interactions between C 2 H 4 and excited O-atoms ( 1 D) generated upon UV-photolysis of CO 2 only confirmed the formation of acetaldehyde and ethylene oxide, while vinyl alcohol formation was not reported. Their experimental results also showed that the excited O-atoms ( 1 D) reacting with C 2 H 2 or C 2 H 6 results in ketene and in acetaldehyde and ethanol, respectively.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…2 and clearly shows the spectral redshift corresponding to species' C 18 O vibrational modes. Besides H 2 18 O 2 signals (i.e., 1384 and 832 cm −1 ), IR features of CH 2 C 18 O (ν 2 ), CH 3 CH 18 O (ν 4 ), CH 2 CH 18 OH (ν 9 ), and CH 3 CH 2 18 OH (ν 11 ) are found at 2106, 1677, 1114, and 1030 cm −1 , respectively (Hawkins & Andrews 1983;Rodler et al 1984;Hudson & Loeffler 2013;Maity et al 2014;Bergner et al 2019). Peak positions due to transitions not directly affected by O-atoms, such as the C-C stretching modes (1662 and 1639 cm −1 ) of CH 2 CH 18 OH and the CH 3 deformation (1351 cm −1 ) as well as the C-C stretching (1133 cm −1 ) mode of CH 3 CH 18 O do not shift more than the 1 cm −1 with respect to the same transitions of the main isotope, which is within our spectral resolution (Rodler et al 1984;Hawkins & Andrews 1983).…”
Section: Com Formation In Experimentsmentioning
confidence: 99%
“…Thanks to the multiple formation pathways, the COM abundances as a whole are not very sensitive to the initial cloud conditions. Formation of CH 3 OH from hydrocarbons has been recently investigated in laboratory experiments, as well (Qasim et al 2018;Bergner et al 2019). The absence of COM emission then could be due to the current temperature structure of the protostellar cores.…”
Section: Variation Among Coresmentioning
confidence: 99%